Modeling students' voice for enhanced quality in online management education. Issue 2 (July 2021) - Efthymiou, Leonidas; Zarifis, Alex
Abstract: This article proposes a transferable model for online learning, based on the principles of social constructivism. The findings have been collected through 'end-of-course feedback surveys', and concern a student-sample of 170 nationalities, residing in 154 countries. All students were registered in cohorts of the same postgraduate programme over a period of four years. The findings throw light on learners' difficulties in different parts of the world; along with practical implications for University decision-makers and instructors. The article's contribution is encapsulated in an eight-pillar learning model, aiming to facilitate educational inclusion, quality enhancement, and promote the benefit of learners. Highlights: Throws light on learners' difficulties in different parts of the world. Offers an online learning model driven by international students' voice. Identifies the context-specific nature of Instructional Design and Quality enhancement. Delineates practical implications for University decision-makers and instructors.